An evaluation of the effects of mindfulness training from the perspectives of wheelchair basketball players - MacDonald, L. A.; Oprescu, F.; Kean, B. M. (Psychology of Sport and Exercise, 2018)
Objectives: Previous research has highlighted that mindfulness training (MT) is associated with an attenuation in physiological stress in wheelchair basketball players during competition. However, players` perceptions of how MT affected their sporting and everyday life were yet to be determined. Therefore, the present study evaluated the perceived impact of an 8-wk MT intervention on wheelchair basketball players by gathering and analysing the perspectives of the participants in the study. Design: Experimental qualitative design. Methods: Eight wheelchair basketball players completed an 8-wk MT intervention (meditations and mindfulness exercises; five times each week) during a competition period. Participants completed an evaluation survey which explored the impact of the MT intervention. Results: 8 wk of MT was beneficial in various aspects of the participants'` everyday lives, games and training in the form of improved concentration, improved sleep, better stress management, awareness, as well as improved foul shooting accuracy and regulation of heart rate. Conclusions: MT may be efficacious in improving both athletic performance and everyday life in para-athletes.